VD_FINDINFO HC / 2014 / 19 vom 13. Dezember 2013 - VD Tribunal cantonal (2013)
ACTION EN LIBÉRATION DE DETTE, SOLIDARITÉ, REPRÉSENTATION DE L'UNION CONJUGALE, CONJOINT | 166 CC, 143 CO, 32 al. 1 CO, 32 al. 2 CO